Cube texture formation during the early stages of recrystallization of Al-1%wt.Mn and AA1050 aluminium alloys. Issue 1 (July 2015) - Miszczyk, M M; Paul, H
Abstract: The cube texture formation during primary recrystallization was analysed in plane strain deformed samples of a commercial AA1050 alloy and an Al-1%wt.Mn model alloy single crystal of the Goss{110}<001> orientation. The textures were measured with the use of X-ray diffraction and scanning electron microscopy equipped with an electron backscattered diffraction facility. After recrystallization of the Al-1%wt.Mn single crystal, the texture of the recrystallized grains was dominated by four variants of the S{123}<634> orientation. The cube grains were only sporadically detected by the SEM/EBSD system. Nevertheless, an increased density of <111> poles corresponding to the cube orientation was observed. The latter was connected with the superposition of four variants of the S{123}<634> orientation. This indicates that the cube texture after the recrystallization was a 'compromise texture'. In the case of the recrystallized AA1050 alloy, the strong cube texture results from both the increased density of the particular <111> poles of the four variants of the S orientation and the ∼40°(∼< 111>)-type rotation. The first mechanism transforms the S def -oriented areas into S rex ones, whereas the second the near S-oriented, as-deformed areas into near cube-oriented grains.